Review of the court of appeal decision in Udo v. Robson & Ors: a call to expanding the frontiers of fundamental rights enforcement law (2021)
This article is aimed at sensitizing the Nigerian Judges and legal practitioners alike to see need to expanding and expounding the frontiers of fundamental rights enforcement procedure law to accommodate joint application for the enforcement of fundamental rights matter in our law courts. Increasing rate of human rights' Violation is alarming. even in tlie democralic regime which requires broad and liberal approach in the interpretation of our laws toforestall injustice. This article concludes by proposing a wayforward in form of judicial activism. This article calls on Court of Appeal to overnde itselfin subsequent appeal(s). This article, again, calls on Supreme Court to decide on this issue.